Instantaneous Functionalization of Chemically Etched Silicon Nanocrystal Surfaces. Issue 22 (11th November 2016) - Mobarok, Md Hosnay; Purkait, Tapas K.; Islam, Muhammad Amirul; Miskolzie, Mark; Veinot, Jonathan G. C.
Abstract: Remarkable advances in surface hydrosilylation reactions of C=C and C=O bonds on hydride‐terminated silicon have revolutionized silicon surface functionalization. However, existing methods for functionalizing hydride‐terminated Si nanocrystals (H‐SiNCs) require long reaction times and elevated temperatures. Herein, we report a room‐temperature method for functionalizing H‐SiNC surfaces within seconds by stripping outermost atoms on H‐SiNC surfaces with xenon difluoride (XeF2 ). Detailed analysis of the reaction byproducts by in situ NMR spectroscopy and GC‐MS provided unprecedented insight into NC surface composition and reactivity as well as the complex reaction mechanism of XeF2 activated hydrosilylation. Abstract : Fast and fluorous : Chemical etching of silicon nanocrystals with xenon difluoride leads to the rapid production of radicals on the nanocrystal surface. These radical‐enriched reactive surfaces can be exploited to functionalize silicon nanocrystals with various alkenes, alkynes, and ketones with unprecedented speed.